Blastic plasmacytoid dendritic neoplasm / Nabia Idaam Mustapa Albakari - Mustapa Albakari, Nabia Idaam (Faculty of Medicine, 2018)
Blastic plasmacytoid dendritic neoplasm (BPCDN) is a rare entity and difficult to diagnose. It is highly aggressive with a poor diagnosis. Early diagnosis may help with treatment. Here, we report a rare case of co-existence of BPCDN with acute myeloid leukemia in bone marrow.